Mometasone furoate nasal spray for the treatment of asthma. (2nd August 2016) - Meteran, Howraman; Backer, Vibeke
ABSTRACT: Introduction : Asthma is a common respiratory disease characterized by airway inflammation, bronchoconstriction and airway hyperresponsiveness and symptoms such as coughing, wheezing, shortness of breath and chest tightness. Allergic rhinitis is a common comorbidity in asthma and glucocorticoids are the key stone in the treatment of both diseases. Mometasone furoate is a potent synthetic steroid with a very high receptor affinity and a low bioavailability and shown to be superior compared to other inhaled corticosteroids. It is not clear whether the use of mometasone furoate nasal spray (MFNS) is associated with an improvement in asthma control. Areas covered : This current paper reviews the current knowledge on the effect of mometasone furoate nasal spray in the treatment of asthma and includes clinical trials in which both subjective and objective outcomes are assessed. Expert opinion : To date, only few clinical studies have investigated the effect of nasal steroids in the treatment of asthma. The studies investigating the effect of MFNS report contradicting results, although the most well-designed study to answer this question finds no improvement in asthma control. Thus, it seems unlikely that asthma guidelines will be influenced by the current knowledge on the effect of MFNS in the treatment of asthma.